Cultivating Textbook Alternatives From the Ground Up: One Public University’s Sustainable Model for Open and Alternative Educational Resource Proliferation - Lashley, Jonathan; Cummings-Sauls, Rebel; Bennett, Andrew B.; Lindshield, Brian L. (International Review of Research in Open and Distributed Learning, 2017)
This note from the field reviews the sustainability of an institution-wide program for adopting and adapting open and alternative educational resources (OAER) at Kansas State University (K-State). Developed in consult of open textbook initiatives at other institutions and modified around the needs and expectations of K-State students and faculty, this initiative proposes a sustainable means of incentivizing faculty participation via institutional support, encouraging the creation and maintenance of OAER through recurring funding, promoting innovative realizations of “educational resources” beyond traditional textbooks, and rallying faculty participation in adopting increasingly open textbook alternatives. The history and resulting structure of the initiative raise certain recommendations for how public universities may sustainably offset student textbook costs while also empowering the pedagogies of educators via a more methodical approach to adopting open materials.